Lectin Purification through Affinity Chromatography Exploiting Macroporous Monolithic Adsorbents - Silva, Josiane E. da; Lima, Clara M.G.; Silva, Debora L. da; Nascimento, Ivonea S. do; Rodrigues, Sarah de O.; Goncalves, Leticia A.; Santana, Renata E.; Khalid, Waseem; Verruck, Silvani; Emran, Talha Bin; Menezes, Irwin R. A. de; Coutinho, Henrique D.M.; et al. (MDPI, 2023)
Growing medical, engineering, biochemical, and biological interest has led to a steady pace of research and development into polymeric monolithic structures with densely interconnected pores for purifying bio compounds. Cryogels, which are generated by freezing a reactive polymerization mixture, are highlighted due to their versatility and low relative cost as microporous, polymeric, monolithic adsorbents. The conversion of cryogels into affinity adsorbents is one possible alternative to their optimal application. Some of the most often utilized supports for immobilizing particular ligands are monolithic columns manufactured with epoxy radicals on their surfaces. The purification of biomolecules with a high degree of specificity, such as lectins and glycoproteins with an affinity for glycosylated groups, has garnered interest in the use of fixed non-traditional beds functionalized with ligands of particular interest. The interaction is both robust enough to permit the adsorption of glycoproteins and reversible enough to permit the dissociation of molecules in response to changes in the solution’s pH. When compared to other protein A-based approaches, this one has been shown to be more advantageous than its counterparts in terms of specificity, ease of use, and cost-effectiveness. Information on polymeric, macroporous, monolithic adsorbents used in the affinity chromatographic purification of lectins has been published and explored.